Flying Low: HR Challenges in the Airline Industry. (Global Business Management Review (GBMR), 2022)
This case study describes the journey of Aakash Airways from a monopolistic environment, showing remarkable profitability, to a point where local and international competition stiffens and operational inefficiencies lead to a significant plunge in company profits. The main concerns for the newlyappointed chairman are to revive the company in order to recover the huge losses, and to prepare the organization to meet the challenges of globalization and stiffer competition. The top management of Aakash Airways now has to focus on overhauling the company’s Human Resource System in order to build sustainable capacity, improve productivity and service quality, and integrate different HR areas, including recruitment, job description, training, performance appraisal and promotion to achieve organizational goals. The issue requires urgent attention since time is of utmost importance, wherein the overall company performance is deteriorating and the fuel costs are expected to rise, making the situation even worse.